Insight into the conformational analysis of 3-phenyl-N-(3-(trimethoxysilyl) propyl)prop-2-en-1-imine (PTP) as a biocidal candidate: In-silico and quantum computational approach - S. Bindhu; Varsha Raj; S. Nanjundaswamy; M. Hemavathi; S. Sandeep; R.R. Arun Renganathan; S.R. Kumaraswamy; C.S. Karthik; P. Mallu; V. Ravishankar Rai (Results in Chemistry, 2023)
A newly synthesized compound, 3-phenyl-N-(3-(trimethoxysilyl) propyl)prop-2-en-1-imine (PTP) is analyzed in detail for structural clarification by mass spectroscopy & FT-IR along with theoretical quantum chemical computations. The conformers of the structure were optimized through DFT to understand the stable conformer (1Z2E) of the structure and their interaction with the protein. The docking studies of the synthesized compound were carried out to determine the interaction with the receptor protein Dihydropteroate synthase protein (PDB ID: 3TZF) which showed very good interactions with various amino acid residues like HIS203, LEU194, LEU40, and so on. Molecular dynamic simulation of the title compound was made to understand the stability of the docked complex. The MM-GBSA calculations verify that the stable conformer (1Z2E) efficiently binds to selected protein to form a stable protein–ligand complex. The in-silico results revealed that in the future PTP can be used for further development, to treat the antibacterial infection.